The new Africans : a guide to the contemporary history of emergent Africa and its leaders; written by fifty correspondents of Reuters News Agency - Taylor, Sidney; Reuters Limited (London : Hamlyn, 1967)
As Reuters first venture into books, the New Africans represents a landmark in the firm's long and distinguished history, and an exciting new departure in the field of 'who i who' reference guide
osc 15/11/2021
Ref
Keywords: Directories; who is who; Africa